The Study of Total Maximum Daily Load of Parit Tiram Using Water Quality Modelling - SHAHRULNIZA, NURUL AISYAH (Progress in Engineering Application and Technology, 2024)
The Total Maximum Daily Load (TMDL) is a crucial regulatory framework in environmental science and management that evaluates and regulates water pollution in rivers, lakes, and other water bodies. It establishes the maximum allowable amount of a specific pollutant that a water system can endure daily without violating predetermined water quality standards. TMDL considers diverse pollution sources, including point sources like industrial discharges and diffuse non-point sources like agricultural runoff. It considers the assimilative capacity of the receiving water body, considering factors like flow rates, temperature, and other pollutants. The TMDL process involves identifying the targeted pollutant, establishing water quality criteria, and determining the current pollutant load through comprehensive monitoring and data analysis. This data is used to allocate permissible pollutant loads to different sources, ensuring adherence to water quality standards. TMDL plays a significant role in advancing sustainable water resource management, contributing to the protection of aquatic ecosystems, public health preservation, and ecological equilibrium of water bodies. It encourages practices that minimize pollution, fostering long-term health and resilience of aquatic environments.